THE SYSTEM WORKING OF METHODS OF NON-DESTRUCTIVE CONTROL OF AVIATION CONSTRUCTIONS - Єременко, В.С.; Переїденко, А.В. (Science-based technologies, 2009)
This report is devoted to realization the automatic data processing system of NDT measuring results using the LabVIEW 8.5 programming environment. System can be used for calculation signal data and certainty value of non-destructive testing.